Intraoperative Radiotherapy for Locally Advanced Rectal Cancer - Kang, Min Kyu (The Korean Society of Coloproctology, 2010)
PURPOSE: Although intraoperative radiotherapy (IORT) is known to be a method that can reduce local recurrence in locally advanced colorectal cancer, it is not widely used. The aim of this study was to report our experience with IORT for locally advanced rectal cancer. METHODS: From 1991 to 1994, nine patients with locally advanced rectal cancer received IORT. External beam radiotherapy was given postoperatively in five patients and preoperatively in three. Seven patients received chemotherapy. IORT was done with 6-MeV or 9-MeV electrons, and 12 Gy was irradiated at the tumor bed. The median follow-up period was 84 months (range, 15 to 208 months). RESULTS: The median age of patients was 51 years (range, 42 to 73 years). All patients had advanced clinical T-stage (cT3/4) cancer. The overall and the disease-free survival rates were 66.7% and 66.7% at 5 years, respectively. One patient developed a local recurrence near the anastomosis site, which was out of the IORT field. Four patients died before the last follow-up; three from distant metastasis and one from secondary primary cancer. Adverse effects related to IORT did not occur. CONCLUSION: Although the number of patients was small in this study, IORT is thought to be safe and effective in reducing local recurrence in locally advanced rectal cancer. However, the role of IORT should be refined in the era of preoperative radio-chemotherapy followed by total mesorectal excision.